Analisis sinonimi dalam ilmu al-dalalah pada presentasi dikelas : pendekatan teori konseptual: Pendekatan Teori Konseptual - zubaidah, siti zubaidah (Maliki Interdisciplinary Journal, 2025)
The analysis of synonyms in the science of al Dalalah applies a conceptual theory approach to understand the relationship between similar words in the Arabic language. In the context of classroom presentations, it is important to identify keywords that reflect key concepts. This research discusses the importance of using synonyms to enrich presentations and enhance students' understanding. Through the appropriate use of synonyms, teachers can expand vocabulary and clarify complex concepts. The results indicate that understanding synonyms plays a significant role in effective communication in the classroom. By grasping the nuances and differences between synonyms, students can improve their ability to understand and use Arabic language more flexibly and accurately. Therefore, this study provides a valuable contribution to Arabic language learning, particularly in enriching teaching methods and deepening students' understanding of word meanings.